(untitled) (Global Journal of Science Frontier Research, 2014)
In this paper we have investigated the whey fermentation at the production of white brine cheese with strain Kluyveromyces marxianus lactis MC 5, using non-conventional substrate whence for receiving of unicellular protein by an ecological clean and wasteless technology. This process is used for dynamic optimisation Neuro-Dynamic Programming theory. With this optimization procedure the quantity product is increased at the end of the process, simultaneously fermentation time is decreased. The producing of lactose with using of cheese whey, which is a waste product at the production of white brine cheese leads to the receiving one of close cycle and an ecological clean and wasteless technology.